ENSINO DE CIÊNCIAS E A ABORDAGEM DA QUÍMICA EM LIVROS DIDÁTICOS DO 6º AO 9º ANO: compreensão da natureza como um todo dinâmico ou fragmentado? - POMPEU, Elvis Vieira (2024)
The National Curricular Parameters (PCNs) guide that the contents of Sciences be worked in an integrated way. The interdisciplinarity and integration of the contents, too, should be expressed in the textbooks of Primary Sciences, given the importance of this didactic resource. Qualitative and documentary research analyzed the collection of science textbooks of the "Araribá Project", selected in PNLD 2017-2019 for use in municipal schools that offer the final years of Basic Education in the urban area of the municipality of Bagre / PA, with the objective of investigating how Chemical Science is approached in these books. The result of the research showed that the chemical knowledge is distributed in all the volumes of the collection and with concentration of the contents of chemistry in the proposed book for the 9th year. In the books of the 6th, 7th and 8th year there are few references to chemical knowledge, with only superficial citations without conceptual availability. Thus, there is a separation in what concerns the knowledge related to Chemistry, Physics and Biology, which can contribute to a fragmented view of the natural sciences. The levels of representation of chemical knowledge (macroscopic, microscopic and symbolic) are present throughout the collection. But in general, the use of the macroscopic level is prioritized through figures, and there is a greater lack of use of the microscopic and symbolic levels in the 6th, 7th and 8th grade books. From the results it is hoped to draw attention to the adequate introduction of Chemistry in Primary Education in an interdisciplinary way and integrated the other Natural Sciences, contributing to the understanding of nature as all dynamic.